The Asia Pacific Region: Leading the Global Recovery Post-GFC? - Burgess, John; Connell, Julia (Routledge, 2013)
In this article, some broad conclusions are presented concerning the global financial crisis (GFC) and change in the Asia Pacific region to date, with a particular focus on change and adjustments to the labour market. In terms of whether the Asia Pacific region is leading the global recovery post-GFC, a number of comparisons are made between the Asia Pacific region, the USA and the European Union that have been prominent in the articles included here in order to answer that question. Lastly, implications for research and practice are outlined.